Pseudoainhum Associated With Lepromatous Leprosy: A Very Rare Association in Modern World - Ahangama Arachchige Nilanga Nishad; Mahathevan Pathman; Seyed Ahamed Uwyse; Ashan Mendis; Prabath Kularathne Abeysundara; Arjuna P. de Silva (Wolters Kluwer Health, 2023)
Introduction:. Pseudoainhum (dactylolysis spontanea) is characterized by the development of a fibrous band around the digit that gradually leads to autoamputation. Digital pain associated with Pseudoainhum may not be evident in patients with neuropathic conditions. Here, we present a rare case of pseudoainhum patient, which describes a very rare association of pseudoainhum with leprosy. Case presentation:. A 48 year old male with lepromatous leprosy, with resorption of digits, charcot joints and tropical ulcers was seen in the clinic. The forth digit of the left hand had a narrowing due to a fibrous band at the 2nd inter phalangeal joint with shiny tethering distal phalanx. He could not recall the duration of the ainhum. He was not suffering from any pain. Discussion:. The current report describes a very rare association of pseudoainhum with leprosy. The case involved a 48-year-old man in the dermatology ward with lepromatous leprosy presenting with a pseudoainhum. Conclusion:. This case highlights the possibility of delayed presentation of patients with pseudoainhum to physicians when the patients have underlying neuropathic conditions that prevent feeling finger pain and cause abnormal appearance of the digits, especially in leprosy.